Mengoptimalkan Manajemen Strategik Untuk Peningkatan Kinerja Guru Dan Tenaga Kependidikan Dalam Menghadapi Digitalisasi - aprili_a Sutiyawati (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2019)
The rapid development of technology in the digital era has encouraged educational institutions to adapt through strengthening more directed and sustainable management systems. This study aims to analyze the implementation of strategic management in improving the performance of teachers and education personnel, as well as its implications for the quality of education in schools. The study focuses on how the processes of planning, implementing, and evaluating strategies are carried out within the context of digitalization, particularly related to enhancing human resource competence, utilizing information technology, and strengthening a collaborative work culture. A qualitative research approach was employed through observation, in-depth interviews, and document analysis. The results indicate that optimal implementation of strategic management supports the improvement of teacher professionalism, the effectiveness of educational staff services, and the efficiency of administrative processes through the use of digital systems. Furthermore, digitalization enhances transparency, timeliness of services, and the quality of internal communication within the school. Overall, the optimization of strategic management significantly contributes to improving education quality, marked by better learning performance, administrative governance, and satisfaction among school stakeholders. These findings affirm that integrating strategic management and digital technology is essential in realizing high-performing schools that are adaptive to contemporary developments. Keywords: Strategic Management, Teacher Performance, Education Personnel, Digitalization, Education Quality.